KOMUNIKASI ELIT PADA PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN DI KABUPATEN ROKAN HILIR TAHUN 2014 (STUDI KASUS KEMENANGAN JOKO WIDODO DAN JUSUF KALLA) - Nefa Andrian; M.Y.Tiyas Tinov (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research was conducted in order to determine the political communication between the political elite at the General Election of President and Vice President in Rokan Hilir in 2014, this study only focused on personal communication that exists in the victory elite pair Joko Widodo and Jusuf Kalla. The main problem in this research is the victory of Joko Widodo and Jusuf Kalla in Rokan Hilir which if in math coalition of parties supporting the pair Joko Widodo and Jusuf Kalla has only 17 seats of the 45 seats available in the membership of the Legislative Council of Rokan Hilir , This research uses the theory of political communication, political communication strategies and theories of political elites. This research uses descriptive analysis method using a qualitative approach. This research using purposive sampling and snowball sampling that interview with the informant as the object information that aims to achieve the goal. Data used in this study are primary data and secondary data obtained through direct observation and interviews with informants research.This research took place in Rokan Hilir , which the District is not the basis of the parties supporting the coalition Joko Widodo and Jusuf Kalla . Political communication that took place in the General Election of President and Vice President this involves political elites inside and outside the winning team of Joko Widodo and Jusuf Kalla.Based on the results of the analysis of the research data in order to uncover and answer research questions related to the communication of the political elite that occurred in the victory of Joko Widodo and Jusuf Kalla at the General Election of President and Vice President in Rokan Hilir in 2014 ago , in this research , the authors will describe the communication that occurs between the political elite , the political elite is meant here is the local political elite and non- elite local politics.Keyword : Political Communication, Political Elite, General Elections of President and Vice President